Sex differences and clinical outcomes, including ventricular tachyarrhythmias, of patients with heart failure with reduced ejection fraction treated with sacubitril/valsartan - Abumayyaleh, Mohammad; Krack, Carina; Demmer, Jonathan; Pilsinger, Christina; Schupp, Tobias; Behnes, Michael; Sattler, Katherine; El-Battrawy, Ibrahim; Hamdani, Nazha; Akin, Ibrahim (Frontiers in Cardiovascular Medicine, 2024)
BackgroundWomen with heart failure with reduced ejection fraction (HFrEF) often experience worse clinical outcomes compared to men, including higher rates of mortality, hospitalization, and congestion. However, the effects of sacubitril/valsartan on these outcomes, as well as on ventricular tachyarrhythmias, have not been well studied in women with HFrEF.MethodsThis study included consecutive series of patients treated with sacubitril/valsartan at University Hospital Mannheim from 2016 to 2020. Baseline and follow-up data were compared between women and men. The endpoints included all-cause mortality, ventricular tachyarrhythmias, all-cause hospitalization, and congestion.ResultsA total of 246 patients were analyzed, comprising 50 (20.3%) women and 196 (79.7%) men. The study population consisted of 34.3% ambulatory patients and 65.7% hospitalized patients admitted for acute decompensated or symptomatic HF. The sex distribution was as follows: among women, 48.6% were ambulatory and 51.4% were hospitalized, while among men, 30.6% were ambulatory and 69.4% were hospitalized. Ischemic cardiomyopathy (ICM) was less common as a cause of heart failure (HF) in women than in men (32% vs. 57.7%, p = 0.001). During the 12-month follow-up, left ventricular ejection fraction (LVEF) improved more significantly in women than in men, increasing from 29.0% (10.0–45.0) to 40.0% (15.0–59.0) in women (p = 0.009) compared to an increase from 28.0% (3.0–65.0) to 33.0% (13.0–60.0) in men. There were no significant differences in all-cause mortality at 12-month between women and men (4% vs. 6.7%; p = 0.742). The results indicated no significant differences between the sexes in the incidence of ventricular tachyarrhythmias [ventricular fibrillation [VF] and sustained ventricular tachycardia [VT]] (4.5% vs. 0.6%; p = 0.121) (2.3% vs. 3.9%; p = 1.00), hospitalizations (70.2% vs. 67.8%; p = 0.769), congestion at 12-month follow-up (11.4% vs. 10.1%; p = 0.762). Female sex was not identified as a predictor for the occurrence of ventricular tachyarrhythmias or mortality rate at 12 months [hazard ratio (HR), 0.586; 95%-confidence interval (CI) 0.17–2.016; p = 0.397] (HR, 1.898; 95%-CI 0.381–9.464; p = 0.434).ConclusionWomen with HFrEF treated with sacubitril/valsartan showed a greater improvement in LVEF compared to men, though clinical outcomes were similar across sexes. Female sex was not a predictor of ventricular tachyarrhythmias or mortality at 12 months.